2020
DOI: 10.1093/brain/awaa117
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident memory T cells invade the brain parenchyma in multiple sclerosis white matter lesions

Abstract: Multiple sclerosis is a chronic inflammatory, demyelinating disease, although it has been suggested that in the progressive late phase, inflammatory lesion activity declines. We recently showed in the Netherlands Brain Bank multiple sclerosis-autopsy cohort considerable ongoing inflammatory lesion activity also at the end stage of the disease, based on microglia/macrophage activity. We have now studied the role of T cells in this ongoing inflammatory lesion activity in chronic multiple sclerosis autopsy cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
155
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 59 publications
15
155
0
1
Order By: Relevance
“…Frischer et al observed perivascular cuffs only in cases with active progressive disease [70]. In the NBB tissue collection, donors with perivascular cuffs in the brainstem had a higher brain stem lesion load and an overall higher proportion of mixed active/inactive lesions [66]. These observations suggest that presence of perivascular cuffing can be regarded as a detrimental phenomenon in advanced progressive MS, a clinical phenotypic entity not associated with attacks of infiltrating lymphocytes from the circulation.…”
Section: T Cells In Ms Normal-appearing White Matter and White Mattermentioning
confidence: 91%
See 4 more Smart Citations
“…Frischer et al observed perivascular cuffs only in cases with active progressive disease [70]. In the NBB tissue collection, donors with perivascular cuffs in the brainstem had a higher brain stem lesion load and an overall higher proportion of mixed active/inactive lesions [66]. These observations suggest that presence of perivascular cuffing can be regarded as a detrimental phenomenon in advanced progressive MS, a clinical phenotypic entity not associated with attacks of infiltrating lymphocytes from the circulation.…”
Section: T Cells In Ms Normal-appearing White Matter and White Mattermentioning
confidence: 91%
“…This enrichment comprised both CD4 + and CD8 + T cells, in which CD8 + T cells were most prevalent [43,[71][72][73]. Interestingly, the ratio of CD8/CD4 T cells was remarkably consistent within a donor between regions investigated [66]. Where brain T cells were located almost exclusively in the PVS in normal-appearing white matter, they infiltrated the parenchyma in both active and mixed active/ inactive lesions (Figure 2) [43,66].…”
Section: T Cells In Ms Normal-appearing White Matter and White Mattermentioning
confidence: 94%
See 3 more Smart Citations